The story teller - Coel, Margaret, 1937- (Coel, Margaret, 1937- Wind River mystery, 1999)
When a sacred record of Arapaho life on the Plains mysteriously disappears from a local museum, lawyer Vicky Holden investigates, uncovering evidence of much deadlier crimes than manuscript theft. Reprint.